Effect of BF839 + earthworm protein supplement on motor and some non-motor symptoms of Parkinson’s disease: a randomized clinical trial - Zeng, Ting; Lin, Chuhui; Deng, Yuhong; Zhu, Weiwen (Frontiers in Neurology, 2024)
Introduction Some studies have found that probiotics have the potential to treat PD, and earthworm protein is a traditional Chinese medicine used for the treatment of PD. The purpose of this study was to evaluate the safety and efficacy of Bacteroides fragilis 839 (BF839) + earthworm protein supplement as an adjunctive therapy for PD and to observe changes in the gut microbiota. Methods Forty-six patients with PD were recruited for a 12-week 1:1 randomized, double-blind, placebo-controlled clinical trial to evaluate changes in motor and some non-motor symptom scores and detect metagenomic changes in the gut microbiota. Results From baseline to 12 weeks, compared with placebo, the trial group showed significant reductions in the United Parkinson’s Disease Rate Scale (UPDRS) total score (−7.74 ± 5.92 vs. –1.83 ± 4.14, p < 0.001), UPDRS part I (−0.72 ± 0.81 vs. –0.20 ± 0.72, p = 0.026), UPDRS part II (−2.50 ± 2.24 vs. –0.22 ± 1.98, p = 0.001), UPDRS part III (−3.43 ± 3.42 vs. –1.33 ± 2.65, p = 0.024), and UPDRS part IV (−1.13 ± 1.19 vs. –0.15 ± 0.57, p = 0.001). Significant reductions in the Hamilton Depression Scale-24 score (−3.91 ± 3.99 vs. +1.15 ± 3.42, p < 0.001), Self-Rating Anxiety Scale scores (−7.04 ± 5.71 vs. –1.23 ± 2.34, p < 0.001), and Constipation scoring system scores (−8.59 ± 4.75 vs. 0.27 ± 1.24, p < 0.001), were also noted. In the trial group, one patient experienced mild eczema and one suffered low blood pressure, which could not be conclusively attributed to supplementation. Compared to the placebo group, the trial group showed a marked increase in Enterococcus faecium and a decrease in Klebsiella. Conclusion This study is the first to report that probiotics plus earthworm protein can remarkably improve the motor and some non-motor symptoms of PD without serious adverse effects. However, further clinical trials and exploration of the underlying mechanisms are required. Clinical trial registration Clinical trial registry http://www.chictr.org.cn/, Identification No: ChiCTR2000035122.